Oocyte-derived growth factors promote development of antrum-like structures by porcine cumulus granulosa cells in vitro - Riho MORIKAWA; Hirohisa KYOGOKU; Jibak LEE; Takashi MIYANO (The Journal of Reproduction and Development, 2022)
Oocytes communicate with the surrounding somatic cells during follicular development. We examined the effects of two oocyte-derived growth factors, growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), on the development of porcine oocyte–cumulus cell complexes (OCCs) in vitro. We collected OCCs from early antral follicles (1.2–1.5 mm) and prepared oocytectomized cumulus cell complexes (OXCs), which were then cultured in a growth medium supplemented with 0–100 ng/ml GDF9 and/or BMP15 for 7 days. In the medium without GDF9 or BMP15, OCCs developed during culture, and approximately 30% of them formed antrum-like structures. GDF9 promoted OCC development and structure formation in a dose-dependent manner. However, OXCs did not form antrum-like structures without growth factors. GDF9 promoted the development of OXCs, and 50 and 100 ng/ml GDF9 promoted the formation of the structures by 8% and 26%, respectively; however, BMP15 did not promote the formation of these structures. OXCs were then cultured with 100 ng/ml GDF9 and various concentrations of BMP15 to investigate their cooperative effects on the formation of antrum-like structures. BMP15 promoted the formation of antrum-like structures in a dose-dependent manner. In conclusion, GDF9 derived from oocytes is probably important for the formation of antrum-like structures in porcine OXCs, and BMP15 cooperates with GDF9 to form these structures.